Fabrication and Characterization of Aluminium-Rice Husk Ash Composite Prepared by Stir Casting Method - Ahamed, Adnan Adib; Ahmed, Rashed; Hossain, Muhammad Benzir; Billah, Masum (Rajshahi University Journal of Science and Engineering, 2016)
Metal Matrix Composites (MMCs) constitute an important category of design and weight-efficient materials. This article highlights on the work where an attempt is taken to fabricate aluminium matrix composite reinforced with rice husk ash (RHA) particles, an agricultural byproduct with high amount of silica. RHA particles, upon analysis, are incorporated into the Al matrix melt by stir casting. Magnesium (~1%) is used as a wetting agent between matrix and reinforcement. 3, 6 and 9% wt. of RHA are added into the matrix. The microstructure analysis reveals the reinforcing particle distribution inside the matrix which indicates successful fabrication of the composites. The density and mechanical properties such as strength and hardness are measured for both unreinforced metal and composites. The results found in the tests show a decrease in density with increasing reinforcement while increasing yield strength, ultimate strength and hardness of the composites with increasing reinforcement from the unreinforced condition.